Catalytic Enantioselective Halocyclizations beyond Lactones: Emerging Routes to Enantioenriched Nitrogenous Heterocycles - Tripathi, Chandra Bhushan; Mukherjee, Santanu (Synlett, 2014)
Electrophilic halogen-induced reactions of unactivated olefins are an important class of transformations, whose catalytic enantioselective variants have surfaced during the past few years as effective means of olefin heterodifunctionalization. This article covers important developments in the area of enantioselective halocyclizations, specifically in the context of the synthesis of nitrogenous heterocycles.
Keywords: asymmetric catalysis; halocyclizations; olefins; heterocycles